Correlation Between School Well-Being and Self-Regulated Learning in Taman State Junior High School 2 Students.: Hubungan Antara School Well Being dan Self Regulated Learning pada Siswa SMPN 2 Taman - Mahesanara, Asha Ayodya; Nastiti , Dwi (Universitas Muhammadiyah Sidoarjo, 2024)
This research was conducted because of the phenomenon of the lack of self-regulated learning that the author encountered in junior high school students such as not having an independent study schedule at home, needing help from friends in doing assignments, not yet having further education targets. This study aims to determine the relationship between school well being and self-regulation learning in junior high school students. His research is a relational quantitative research. 270 research samples were taken from 1119 students based on the Issac & Michael table with a significance of 5%, and the sampling technique used proportinated stratified random sampling. Data collection was carried out using the scale of school well being and self regulated learning. Data analysis used simple regression statistical analysis with the JASP program. The results of the analysis show the correlation coefficient F = 44.954, p=0.001. This result means that the hypothesis is accepted, namely that there is a positive relationship between school well being and self-regulated learning in junior high school students. Keywords: School Well Being, Self Regulated Learning, Middle School Students